2016
DOI: 10.2196/mhealth.5418
|View full text |Cite
|
Sign up to set email alerts
|

Using Personal Mobile Phones to Assess Dietary Intake in Free-Living Adolescents: Comparison of Face-to-Face Versus Telephone Training

Abstract: BackgroundTraditional paper-based methods to assess food intake can be cumbersome for adolescents; use of mobile phones to track and photograph what they eat may be a more convenient, reliable, and compelling way to collect data.ObjectiveOur aims were to determine (1) the feasibility of using personal mobile phones to send food records with digital images (FRDIs) among free-living adolescents and (2) whether the quality of food records differed between a high-level intervention group (ie, face-to-face training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Previous research into smartphone apps, personal digital assistants (PDAs), or short messaging service (SMS) interventions have attempted to assess participant experience, usually through questionnaires, and report on domains such as user satisfaction, patterns of usage, engagement, reasons for like or dislike, helpfulness, and influence on self-efficacy [ 33 , 35 , 44 - 50 ]. Studies in adolescent groups have examined the barriers and facilitators of using smartphone apps to record diet [ 42 ], using mobile technology (photos, emails, and texts) to record diet [ 41 ], and using diet recording apps for weight control [ 40 ]. These studies have also explored the effect of using different training methods (face-to-face vs telephone) [ 41 ] and the use of technology alone versus technology and counseling [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research into smartphone apps, personal digital assistants (PDAs), or short messaging service (SMS) interventions have attempted to assess participant experience, usually through questionnaires, and report on domains such as user satisfaction, patterns of usage, engagement, reasons for like or dislike, helpfulness, and influence on self-efficacy [ 33 , 35 , 44 - 50 ]. Studies in adolescent groups have examined the barriers and facilitators of using smartphone apps to record diet [ 42 ], using mobile technology (photos, emails, and texts) to record diet [ 41 ], and using diet recording apps for weight control [ 40 ]. These studies have also explored the effect of using different training methods (face-to-face vs telephone) [ 41 ] and the use of technology alone versus technology and counseling [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was already demonstrated that FFQ isoflavones estimates are significantly correlated with urinary isoflavonoids in a cohort of adults that includes parents of some of these adolescents [30]. The use of digital photographs in food records made this method less burdensome to respondents; however, managing the texts/digital photographs and quality control of the digital photograph-assisted FR on the part of the research team was still time-consuming [28]. Likewise, although human intervention in ascertaining the accuracy of food records submitted by participants is a strength, it is still subject to several errors, i.e., judgment, inter-evaluators, and coding.…”
Section: Discussionmentioning
confidence: 99%
“…As the criterion measure for this study, we determined the feasibility of using personal mobile phones for photographing foods to be consumed and recording intake as part of the food recording process among our young study participants. This method is described in a forthcoming article [28]. Instead of consecutive days of recording, the protocol was designed to reduce the burden associated with continuous food recording which may result in deviation from usual intake [27] or boredom, and to make the procedure more attainable among adolescents.…”
Section: Food Records With Digital Photographsmentioning
confidence: 99%
“…At-home data collection could provide a better picture of real-life situations. Web-based data collection was reviewed by Swan [ 3 ] as an important emerging complement to clinical trials. Addition of a more standardized, organized design is recommended for more reliable data than by various crowdsourced data collections.…”
Section: Introductionmentioning
confidence: 99%